2019
DOI: 10.1080/09585192.2019.1579245
|View full text |Cite
|
Sign up to set email alerts
|

Whom do you know? Recruiters’ motives for assessing jobseekers’ online networks

Abstract: Network recruitment has become an essential part of the modern labour market. However, there are significant research gaps: 1) the development of social media has been crucial to the growth of social networks, yet we know little about its influence on network recruitment; 2) studies on network recruitment generally focus on employees' rather than employers' perspectives; 3) the context of most research is the US labour market, which then identifies a need for contributions relating to other countries. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…As downsizing spread in the 1980s, employees engaged in a positive self-presentation activity and reframed their value explicitly in their resumes; consequently, employers began to distrust the information that prospective employees shared (Barrick et al, 2009;Berkelaar, 2014). Hedenus et al (2019) found that cybervetting helps employers determine whether the candidate is trustworthy. For example, employers assess a job candidate's online connections to see if there are any mutual connections to assess trustworthiness (Berkelaar & Buzzanell, 2015).…”
Section: Research-article20202020mentioning
confidence: 99%
“…As downsizing spread in the 1980s, employees engaged in a positive self-presentation activity and reframed their value explicitly in their resumes; consequently, employers began to distrust the information that prospective employees shared (Barrick et al, 2009;Berkelaar, 2014). Hedenus et al (2019) found that cybervetting helps employers determine whether the candidate is trustworthy. For example, employers assess a job candidate's online connections to see if there are any mutual connections to assess trustworthiness (Berkelaar & Buzzanell, 2015).…”
Section: Research-article20202020mentioning
confidence: 99%
“…level of education, certifications, etc.). However, current research attempts to incorporate more multi-dimensional scales and now suggests that education may not be a key to hiring individuals and networks and connections are the most important (Tandon et al, 2018), social capital level within China will have the greatest effect on the hiring decision (Zhang and Lin, 2016), that recruiters use a potential candidate's social capital by measuring their online network's size and composition (Hedenus et al, 2019) and use of guanxi in recruitment practice can overcome the liability of smallness (Ko and Liu, 2017). Our research attempts to support signalling theory through a direct, immediate test of a signal to a reaction by receivers.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recruiters may also check the networks (friend lists and contact lists) that job seekers have on their social media profiles, in order to assess their social capital and the size of their professional networks. Some recruiters also evaluate how applicants interact with other social network users, as an informal confirmation of their social competencies [33].…”
Section: The Importance Of Visual and Textual Cues For Cybervettingmentioning
confidence: 99%